Hydrogen sulphide reduced the accumulation of lipid droplets in cardiac tissues of db/db mice via Hrd1 S‐sulfhydration. Issue 19 (25th September 2021) - Sun, Yu; Zhang, Linxue; Lu, Baoling; Wen, Jingchen; Wang, Mengyi; Zhang, Shiwu; Li, Qianzhu; Shu, Feng; Lu, Fangping; Liu, Ning; Peng, Shuo; Zhao, Yajun; et al.
Abstract: Accumulation of lipid droplets (LDs) induces cardiac dysfunctions in type 2 diabetes patients. Recent studies have shown that hydrogen sulphide (H2 S) ameliorates cardiac functions in db/db mice, but its regulation on the formation of LDs in cardiac tissues is unclear. Db/db mice were injected with NaHS (40 μmol·kg ‐1 ) for twelve weeks. H9c2 cells were treated with high glucose (40 mmol/L), oleate (200 µmol/L), palmitate (200 µmol/L) and NaHS (100 µmol/L) for 48 hours. Plasmids for the overexpression of wild‐type Hrd1 and Hrd1 mutated at Cys115 were constructed. The interaction between Hrd1 and DGAT1 and DGAT2, the ubiquitylation level of DGAT1 and 2, the S‐sulfhydration of Hrd1 were measured. Exogenous H2 S ameliorated the cardiac functions, decreased ER stress and reduced the number of LDs in db/db mice. Exogenous H2 S could elevate the ubiquitination level of DGAT 1 and 2 and increased the expression of Hrd1 in cardiac tissues of db/db mice. The S‐sulfhydration of Hrd1 by NaHS enhanced the interaction between Hrd1 and DGAT1 and 2 to inhibit the formation of LD. Our findings suggested that H2 S modified Hrd1 S‐sulfhydration at Cys115 to reduce the accumulation of LDs in cardiac tissues of db/db mice.